Development of Three Recombinase Polymerase Amplification Assays for the Rapid Visual Detection of Spiroplasma eriocheiris - Yunji Xiu; Ruixin Feng; Zongrui Yang; Lirong Jiang; Yiping Lin; Qingyue Xu; Dong Zheng; Shun Zhou (Journal of Fish Diseases, 2025)
Spiroplasma eriocheiris is a pathogen in the Chinese mitten crab Eriocheir sinensis and is associated with tremor disease. S. eriocheiris infects virtually all artificially bred crustaceans, resulting in significant economic losses to the aquaculture industry in China. Recombinase polymerase amplification (RPA) is considered a promising technology for the rapid and sensitive detection of disease. For the rapid detection of S. eriocheiris , this study established basic RPA, RPA‐EXO and RPA‐LFD, which were visualised via agarose gel electrophoresis, SYBR Green I, fluorescence signals and test lines on lateral flow dipsticks. Specific primers and probes were designed based on the 16S ribosomal RNA sequence of S. eriocheiris . The optimal primer pairs for the basic RPA, RPA‐EXO and RPA‐LFD were RPA‐F3/R3, RPA‐F3/R3 and RPA‐LFD‐F3/R3, respectively. The optimal temperatures and times of basic RPA, RPA‐EXO and RPA‐LFD were 37°C for 25 min, 39°C for 30 min and 39°C for 10 min, respectively. The specificity test indicated that in addition to the positive test results for S. eriocheiris , the other five DNA templates tested negative, demonstrating strong specificity. The results of the sensitivity test revealed that the detection limits of RPA, RPA‐EXO and RPA‐LFD were 5.77 × 10 −2 , 5.77 × 10 −4 and 1.52 × 10 −6 ng/μL, respectively, indicating high sensitivity. This study established three methods for the detection of S. eriocheiris that are characterised by a constant temperature, rapid response, high sensitivity and strong specificity.